Epidemiology and Outcomes of Congenital Anomalies Requiring Surgery in Infants in Saudi Arabia - Dr. Khaled Husain AlFaifi, Dr. Faris muteb sh. Al-mutairi, Dr. Abeer Seadan Alrashedi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Congenital anomalies are a significant cause of infant mortality and disability globally. This retrospective study analyzed the epidemiology, mortality, and outcomes for congenital anomalies requiring surgery in infants under 1 year in Saudi Arabia. Medical records were reviewed for 250 infants undergoing surgery for congenital anomalies at two major hospitals in Riyadh from 2010-2020. The most prevalent anomalies were congenital heart defects (32%), neural tube defects (27%), and gastrointestinal malformations (17%). Overall mortality rate was 10.8%, highest for abdominal wall defects (25%) and lowest for cleft lip and palate (2%). Median hospital stay was 26 days; infants with respiratory anomalies had longer stays (median=36 days). Postoperative complications occurred in 18% of cases, most commonly infection (12%). Congenital anomalies remain a major contributor to infant morbidity and healthcare costs in Saudi Arabia. Mortality and outcomes vary by anomaly type. Further studies on risk factors and improving management are warranted to optimize congenital anomaly prevention and treatment